Economic Dependence: An Analysis of Cooperation Between Iraq and Iran in the Energy Sector 2003-2022 - Ahmad, Hanif Suryadi (Jurnal Locus Penelitian dan Pengabdian, 2025)
Dependency is a topic that still requires in-depth study. It should be understood that the study of dependency is an important factor not only in relation to a country's economic growth but also in shaping the political direction between one country and another. This research aims to examine specifically the factors that drive Iraq to collaborate with Iran in the energy sector, using foreign policy decision-making theory as the analytical framework. The method applied in this research is qualitative. Data collection was conducted through a triangulation technique involving literature and document studies, followed by analysis to establish the validity of the data. The research findings concluded that the cooperation agreement between Iraq and Iran in the energy sector resulted from two main reasons: (1) the rise of the Arab Syiah group, which dominates politics in Iraq alongside the expansion of Iran’s influence and regional proximity; and (2) the gap between electricity supply and domestic demand.